Sosialisasi dan Pendampingan Pembuatan Sertifikat Halal untuk Kelegalitasan Usaha UMK Dina Dewi - Rosikhu, Muhammad; Karni, Ine; Komalasari, Husnita; Cahyadi, Irwan (PPPM POLTESA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy. However, challenges related to legal status and halal certification often hinder the development of these businesses, particularly for MSMEs in the food and beverage sector. This community service activity aims to provide socialization and assistance in obtaining halal certification for UMK Dina Dewi in Peresak Village, West Lombok, using the Online Single Submission (OSS) system and Integrated One-Stop Service (PTSP-Halal). The methods employed include lectures, discussions, and work instructions. The results show an increase in participants' understanding of the importance of business and product legality, completion of administrative documents such as the Halal Product Guarantee System, and the issuance of halal certificates for three UMK Dina Dewi food products: keciprut, tempani, and kaliadem. Technical assistance successfully addressed challenges such as limited technology literacy and understanding of administrative processes, enabling MSMEs to independently manage their business legality. Registration for this certification was conducted through the government program, the free halal certification (SEHATI). This activity not only enhances the competitiveness of MSMEs in local and international markets but also serves as a strategic step in fostering inclusive and sustainable economic empowerment.